2015
DOI: 10.1007/s11255-015-1156-0
|View full text |Cite
|
Sign up to set email alerts
|

Lateroconal fascia suspension for management of peritoneal tear and “curtain” effect during retroperitoneal laparoscopic operations

Abstract: Lateroconal fascia suspension method could manage most peritoneal tears and curtain effect effectively during retroperitoneal laparoscopic operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…When Gerota fascia was incised longitudinally close to the dorsal side, the remaining fascia was retracted to the ventral side and affect exposure of ventral field of view. Yin et al ( 7 ). reported that they performed LFS procedure in 30 cases of retroperitoneal laparoscopic surgery including adrenalectomy (12 cases), PN (9 cases) and radical nephrectomy (9 cases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Gerota fascia was incised longitudinally close to the dorsal side, the remaining fascia was retracted to the ventral side and affect exposure of ventral field of view. Yin et al ( 7 ). reported that they performed LFS procedure in 30 cases of retroperitoneal laparoscopic surgery including adrenalectomy (12 cases), PN (9 cases) and radical nephrectomy (9 cases).…”
Section: Discussionmentioning
confidence: 99%
“…Retroperitoneal workspace was created with finger by pushing forward the peritoneum and pressure-balloon from surgical glove mounted on a red catheter (diameter was 4 mm). The other two ports were inserted at anterior and posterior axillary line close to costal line under the direct view ( 3 , 7 , 8 ). The CO 2 pressure was maintained at 15 mmHg during the surgical procedure.…”
Section: Methodsmentioning
confidence: 99%